Description of the larva and redescription of the adult of Kempnyia neotropica Jacobsen and Bianchi (Plecoptera : Perlidae) with biological notes - Bispo, Pitagoras C. [UNESP]; Froehlich, Claudio G. (Taylor & Francis Ltd, 2008)
Kempnyia neotropica is the species with the widest distribution in this genus. In this work, samples collected in the states of Gois, Minas Gerais and So Paulo were analysed, confirming that all belong to a single species. The larva is described, the adult is redescribed and biological notes are presented.
Keywords: stoneflies; Kempnyia; Neotropical; Brazil